A PRAGMATIC ANALYSIS OF ILLOCUTIONARY ACTS IN USTADZ ABDUL SOMAD’S SPEECH ON THE 2024 GENERAL ELECTION - Srimaharani Tanjung; Ami Nurasid; Anggi B Malau; Meylin A.D. Siburian; Sondang Manik (English Education Department at FKIP Nommensen University, 2026)
This study examines the pragmatic functions of Ustadz Abdul Somad’s (UAS) speech regarding the 2024 General Election. The research aims to identify the specific types of illocutionary acts employed and analyze how these linguistic choices construct a persuasive message for a peaceful election. Utilizing a qualitative approach, the dataset consists of one full-length video lecture (approximately 60 minutes) retrieved from YouTube. Data were analyzed using John Searle’s Speech Act Theory through a three-stage coding procedure: data reduction, categorization based on illocutionary functions, and contextual interpretation. The findings indicate a predominance of directive speech acts, which UAS uses to explicitly urge voters and election organizers (KPU) to uphold the LUBER JURDIL principles. By prioritizing directives over other acts, the speaker transforms a religious lecture into a practical call for civic responsibility. While this study is limited to a single speech by one prominent figure, the findings provide a framework for religious preachers to communicate political neutrality. These results contribute to the field of pragmatics by demonstrating how religious authority is leveraged to promote intelligent voting behavior and mitigate money politics in a democratic transition.